KARAKTERISTIK MINUMAN PROBIOTIK SARI JAMBU BIJI MERAH DENGAN PENAMBAHAN EKSTRAK KAYU MANIS DAN KAYU SECANG - Fibra Nurainy; Samsul Rizal; Suharyono Suharyono; Esa Susanti (Politeknik Negeri Lampung., 2022)
Red guava was a potential fruit that could be used as raw material for probiotic drinks. The addition of spices such as cinnamon and sappan wood could increase the acceptance of its sensory properties as well as its functional benefits. This study aims to determine the effect of spices (cinnamon and sappan wood) and spice concentration on total lactic acid bacteria, total acid, pH and sensory properties of red guava juice probiotic drink fermented with Lactobacillus casei bacteria. The treatments were arranged in a Completely Randomized Block Design (RAKL) with two factors and three replications. The first factor was the type of spice which consists of cinnamon (J1) and sappan wood (J2). The second factor was the concentration of spices, namely 1% (K1), 2% (K2), 3% (K3), 4% (K4), and 5% (K5).The data were analyzed by comparison test and orthogonal polynomial (OP/OC) at 5% level. The results showed that the type of spice (cinnamon and sappan wood) significantly affected the total lactic acid bacteria (LAB), total lactic acid, aroma, and overall acceptance of the red-spiced guava juice probiotic drink. Spice concentration had a significant linear effect on total lactic acid bacteria (LAB), total lactic acid, pH, and aroma, quadratic effect on taste and overall acceptance of red guava juice probiotic drink. The addition of 3% cinnamon extract resulted in a red-spiced guava juice probiotic drink with the best characteristics with a total LAB of 10.93 log cfu/ml; titrable acidity of 0.49%; pH of 4.25; hedonic taste score of 3.31 (medium like); hedonic aroma score of 3.24 (medium like); and an overall acceptance score of 3.53 (likes).